2014
DOI: 10.1111/jfb.12372
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal and life‐phase related differences in growth in Scarus ferrugineus on a southern Red Sea fringing reef

Abstract: Temporal trends in growth of the rusty parrotfish Scarus ferrugineus were studied on a southern Red Sea fringing reef that experiences seasonal changes in environmental conditions and benthic algal resources. Length increment data from tagging and recapture were compared among periods and sexes and modelled using GROTAG, a von Bertalanffy growth model. The growth pattern of S. ferrugineus was highly seasonal with a maximum occurring between April and June and a minimum between December and March. Body conditio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 74 publications
0
2
0
Order By: Relevance
“…While this model has been used in other studies (e.g., Francis ; Wilde and Sawynok ; Afeworki et al. ), it is used rarely and those studies have been primarily with marine species that were largely of commercial or recreational interest. We showed that the model can be used to derive useful estimates of growth rates and growth model parameters for an imperiled species for which individuals cannot be legally or ethically sacrificed to remove calcified structures for estimating age.…”
Section: Discussionmentioning
confidence: 99%
“…While this model has been used in other studies (e.g., Francis ; Wilde and Sawynok ; Afeworki et al. ), it is used rarely and those studies have been primarily with marine species that were largely of commercial or recreational interest. We showed that the model can be used to derive useful estimates of growth rates and growth model parameters for an imperiled species for which individuals cannot be legally or ethically sacrificed to remove calcified structures for estimating age.…”
Section: Discussionmentioning
confidence: 99%
“…This is valid if reproduction reduces growth or increases mortality of the STPs (Iwasa, ). The present study, however, shows that transitional individuals and STPs have the fastest growth in S. ferrugineus (Afeworki et al ., ) suggesting that their reproductive activity does not affect their growth negatively. This is plausible since STPs do not spend energy for territorial defence.…”
Section: Mean Fork Length (Lf) and Sample Sizes (N) Of Scarus Ferrugimentioning
confidence: 99%